Modeling a pumped storage hydropower integrated to a hybrid power system with solar-wind power and its stability analysis. (15th August 2019) - Xu, Beibei; Chen, Diyi; Venkateshkumar, M.; Xiao, Yu; Yue, Yan; Xing, Yanqiu; Li, Peiquan
Highlights: We propose a unified model of the pumped storage station at the turbine condition. Parametric uncertainty on the output contribution are quantized. A novel voltage source converter controller is designed for the solar-wind power. We validate this model against the existing model and operational data. Abstract: Renewable energy integrated into electric power systems, such as hydropower, solar, and wind power, has been the primary choice for many countries. However, both wind power generation and photovoltaic power generation have strong randomness, volatility and intermittency. Large-scale of them connected to grid proved both a threat and a challenge for the safe and stable operation of electric power systems. Pumped storage stations integrated to a hybrid power system with solar and wind power for China are under construction to tussle with this challenge. Historically, modeling of a pumped storage station integrated a hybrid power system has been ignored the interaction effect between the shaft vibration and the governing strategies, which will increase the dynamic risk of the pumped storage station disconnected immediately to the hybrid power system. Here we unify the models of the hydro-turbine governing system and the hydro-turbine generator unit with a novel expression of the hydraulic force. A hybrid power system model with solar-wind-hydro power is established using Matlab/Simulink. Furthermore, we quantify all the parameter's interaction contributions of the pumped storage station integrated to the hybrid power system with the extended Fourier amplitude sensitivity text method and validate this model with the existing models. Finally, we show the feasibility of the pumped storage station model in integrating the hybrid power system under steady and fault scenarios.